Language loyalty and ethnolinguistic solidarity of members of the Slovak language community in Vojvodina - Sokolović Dalibor A. (Južnoslovenski Filolog, 2017)
This paper analyses the impact of linguistic loyalty and solidarity on the preservation of the Slovak language community in Vojvodina. These factors represent an essential element in the model of linguistic description of a language community in a minority position. In the first part of the paper, we present the structure and components of ethnolinguistic solidarity of the Slovak community in Vojvodina, and in the second we show results of the survey conducted in 2014 among members of the community related to the level of their linguistic loyalty. Language attitudes of members of the Slovak language community in Vojvodina presented in this analysis bring us new insight into the structure of ethnolinguistic solidarity and reveal the reasons and motivation of their linguistic loyalty, or the absence of it. Vojvodinian Slovaks consider their own language as the most important constituent of their ethnicity, but the survey nonetheless also identified characteristics of the initial phase of the process of language relativisation, as well as a reduction of its role as the cultural marker of the community.